IMPLEMENTATION OF VIRTUAL TOUR USING IMAGE STITCHING AS AN INTRODUCTION MEDIA OF SMPN 1 KARANGKOBAR TO NEW STUDENTS - Reza Setiawan, Muhammad; Azrino Gustalika, Muhamad; Lulu Latif Usman, Muhammad (Informatika, Universitas Jenderal Soedirman, 2023)
“During the pandemic, the education sector experienced a decline where students and teachers had to do online learning due to the increasingly widespread Covid-19 outbreak. Therefore, the Indonesian government decided to reduce activities that cause crowds in order to prevent the transmission of Covid-19 in Indonesia. With such problems, the author can provide a solution by using a Virtual Tour which is used as a medium to introduce Karangkobar 1 State Junior High School to students who want to register when PPDB takes place. Virtual Tour in the form of 360-degree panoramic images provided with a hotspot and several features such as popups such as images and information that appear in real time. In the functional testing of the Espensaka Virtual Tour application, it was carried out using the Blackbox Testing method on eight different smartphones which produced functions that could run well but had problems with the Gyroscope which could not run on laptops and computers. Then the test using the SUS (System Usability Scale) method with 90 respondents who filled out 10 questions on the questionnaire resulted in an average value of 73.8 which the score according to the System Usability Scale Grade was included in a good rating. From the results of testing using the method on the application, it can be concluded that the Espensaka Virtual Tour application can be run well but has problems with the Gyroscope which cannot be run on laptops and computers. The Espensaka Virtual Tour application can still be used by making an improvement on the recommended hotspot.